Diakonia i charyzmat: Fenomen macierzyństwa Maryi w ujęciu Edwarda Schillebeeckxa i Czesława Bartnika = Diakonia and Charism : The Phenomenon of Mary’s Motherhood as Seen by Edward Schillebeeckx and Czesław Bartnik - Nadbrzeżny, Antoni (Verbum vitae, 2024)
The purpose of this article is to compare the views of Edward Schillebeeckx (1914-2009) and Czesław Bartnik (1929-2020) on the essence of Mary’s divine motherhood. Both are prominent and original European theologians. The Flemish Dominican represents a more ‘bottom-up’ Mariology of the phenomenological and existentialist approaches. The Polish professor, on the other hand, is known as a proponent of personalistic Mariology. The article uses a comparative theological method. The results of the analysis show that Schillebeeckx and Bartnik proposed different Mariological interpretations. According to Schillebeeckx, Mary’s motherhood has a sacramental, epiphanic and diakonia character. Bartnik, on the other hand, believes it to be primarily personalistic, relational and charismatic. Despite their clear differences, the two concepts can be considered largely complementary. In the final section, the author proposes his own conception, which he calls axiological-symbolic. He portrays Mary’s motherhood as an event-symbol to be properly read in the light of the contemporary signs of the times.